2001
DOI: 10.1046/j.1460-9592.2001.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Detection of Supraventricular Arrhythmias by Implantable Dual Chamber Defibrillators: A Comparison of Four Different Algorithms

Abstract: Inappropriate therapy of supraventricular tachyarrhythmias by an ICD is still a common problem. Dual chamber (DDD) ICDs provide additional atrial sensing and should result in higher specificity for detection of supraventricular tachyarrhythmias. However, a direct comparison of different dual chamber algorithms has not been reported. The detection algorithms of four different DDD ICDs were tested: Phylax AV, Defender IV, Ventak AV III DR, and Gem DR 7271. Based on arrhythmias recorded from patients undergoing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…Dual-chamber ICD systems were used approximately as commonly in patients who experienced an inappropriate shock (38.6%) as in those who did not (44.4%, Table 3). Prior studies have often failed to show a benefit of dualchamber devices in preventing inappropriate detections of supraventricular arrhythmias (22,26,35,36). The Detect Supraventricular Tachycardia Study (DETECT SVT) recently showed a reduction in the percent of total SVT episodes that were inappropriately classified as VT in the dualchamber detection group (30.9%) than the single-chamber group (39.5%) (37).…”
Section: Outcomes Of Patients Experiencing Inappropriate Shocksmentioning
confidence: 99%
“…Dual-chamber ICD systems were used approximately as commonly in patients who experienced an inappropriate shock (38.6%) as in those who did not (44.4%, Table 3). Prior studies have often failed to show a benefit of dualchamber devices in preventing inappropriate detections of supraventricular arrhythmias (22,26,35,36). The Detect Supraventricular Tachycardia Study (DETECT SVT) recently showed a reduction in the percent of total SVT episodes that were inappropriately classified as VT in the dualchamber detection group (30.9%) than the single-chamber group (39.5%) (37).…”
Section: Outcomes Of Patients Experiencing Inappropriate Shocksmentioning
confidence: 99%
“…However, the incidence of inadequate therapies or the withdrawal of adequate therapy delivery still remains a major problem [1][2][3][4]17], although sophisticated tachycardia discrimination algorithms have been implemented to the devices.…”
Section: Discussionmentioning
confidence: 99%
“…Supraventricular tachyarrhythmia are still the main cause for inappropriate therapy delivery in 8% to 22% of patients with implantable cardioverter defibrillators (ICD) [1,2], leading to patient discomfort or severe proarrhythmia [3,5]. Therefore, enhanced detection algorithms such as the sudden rate increase (''sudden onset''), the rate stability, or the morphology discrimination criterion have been implemented to modern ICDs [6 -8].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies directly comparing the efficiency of the available algorithms are lacking [21,22]. Hintringer et al [23] tested four different dual-chamber algorithms by simulating various supraventricular tachycardias and VTs recorded during electrophysiologic studies. All devices revealed a very low specificity, ranging from 11% to 28% for all supraventricular arrhythmias.…”
Section: Potential Pitfalls In Dual-chamber Algorithmsmentioning
confidence: 99%